The Nuremberg Trial Against the Major German War Criminal Before the International Military Tribunal (1945-1946) - Safferling, Christoph (Dealing with Totalitarian Regimes and Human Rights, 2024)
The Nuremberg Trial is recognised as the basis of modern international criminal law. In less than one year, the four allied powers which had pursued a costly victory over Nazi Germany presented convincing evidence for the German aggression crimes before the International Military Tribunal. This chapter contains a brief outline of this revolutionary international criminal trial, its accused, the core crimes, and the procedure. It also takes up criticism that was formulated particularly by German defence lawyers, scholars and politicians even decades after the termination of the trials, like the non-retroactivity principle or the ´victors justice´- denunciation. Ultimately, it puts the Nuremberg Trial into the perspective of a further reception of the Nazi past of Germany as well as the development of international criminal law in this respect. <br
Keywords: Nurember Trial; International Criminal Law; Nazi Germany